Changes in some religious practices of the Holy Catholic Apostolic Roman Church as influenced by socio-economic and political conditions in the world - Garcia, Dolores Garcia 1934- (1962)
It is the changes in some religious practices of the Holy Catholic Apostolic Roman Church which are affected by socio-economic and political conditions in the world from the third century to the present that the author attempted to determine. Some of the conditions are (1) the union between the Church and the State; (2) the subsequent seperation on the two factions (3) the Religious Reformation of the sixteenth century and (4) the industrial revolution which was accompanied by significant socio-economic changes.